“The Big Resilient” : école et rebranding dans l’après-Katrina - Laurie BÉREAU (E-REA)
This paper focuses on the reconstruction of New Orleans after Katrina through the lens of the transformation of the city’s school system. When New Orleans commemorated the hurricane’s 10th anniversary, the outcome was not as bleak as one could have expected based on the first response to the disaster and the initial reconstruction efforts. Against all odds, the city has partially managed to overcome the shock it had gone through and now builds up on its image of resilience. The switch to an almost all charter school system has been highly publicized as a sign of New Orleans’ willingness to move forward and become a leading city in terms of innovation and entrepreneurship. Here we will show how the metamorphosis of the educational landscape, which hinges greatly on notions of liberalism and individual initiative, has participated in the rebranding of New Orleans. The question remains whether this reform, partially driven by the will to speed up the revitalization of the city and to revamp its image on a larger scale, affects the actual resilience of communities and neighborhoods in the field.